Changes in Methods of Bequest Among the Malays: The Impact of Islam - Mohamed, Asjad; Sulong, Jasni (Melayu: Jurnal Antarabangsa Dunia Melayu, 2016)
This paper aims to study the methods of bequest before and after the colonial period, as well as the impact of colonialism on the Malays in the Malay States of the Peninsula. Apart from revealing the history of the methods of bequest according to the customs and traditonal laws of the Malays, this article also takes a detailed look at the changes and developments in the methods of bequest after the arrival of Islam. This is a qualitative study which was conducted using library research. The findings of the study show that the arrival of Islam solved issues concerning the administration of wills, as well as bringing an end to disputes and enmity among heirs. Islam brought with it complete inheritance laws that resulted in greater awareness in Malay society, and that hitherto influenced methods of bequest among the Malays. Keywords: bequests, society, Tanah Melayu, custom, law